Sixth Review of the Fund's Data Standards Initiatives. (Policy Papers; Policy Paper ;, 2005)
The Data Standards Initiatives, the SDDS and the GDDS, have achieved the goals the Executive Board set in its Fifth Review of July 2003. The staff sees the next three years as a period of consolidating these gains by maintaining the credibility of the SDDS through improved monitoring of countries' observance of its requirements, and further integrating both the SDDS and GDDS under the Fund's Data Quality Program (DQP) by aligning their structure with the Fund's Data Quality Assessment Framework (DQAF). The staff proposes to include no new data categories in the SDDS and GDDS. Instead, the staff proposes to deepen descriptive information on how countries cover oil and gas activities and products in selected existing data categories.